HLA‐B*13:95, a novel variant of HLA‐B*13, discovered in a Taiwanese blood donor. (27th November 2016) - Yang, K. L.; Lin, P. Y.
Abstract : A single nucleotide replacement at residue 430 of HLA‐B*13:01:01 results in a new allele, HLA‐B*13:95 .